Predicting prognosis and immune responses in hepatocellular carcinoma based on N7-methylguanosine-related long noncoding RNAs - Dai, Yu-yang; Gao, Yi-ping; Chen, Lin-xin; Liu, Jin-song; Zeng, Cheng; Zhou, Jian-dong; Wu, Hong-lin (Frontiers in Genetics, 2022)
Background: Hepatocellular carcinoma (HCC), which has high rates of recurrence and metastasis and is the main reason and the most common tumor for cancer mortality worldwide, has an unfavorable prognosis. N7-methylguanosine (m7G) modification can affect the occurrence and progression of tumors by affecting genes expression and other biological functions. Additionally, many previous studies have confirmed the remarkable fuction of long noncoding RNAs (lncRNAs) in tumor progression; however, limited studies have explored the effects of m7G-related lncRNAs in patients with HCC. Methods: Relevant RNA expression information was obtained from The Cancer Genome Atlas (TCGA, https://portal.gdc.cancer.gov), and m7G-related lncRNAs were identified via gene coexpression analysis. Subsequently, univariate Cox regression, LASSO regression, and multivariate regression analyses were implemented to construct an ideal risk model whose validity was verified with Kaplan–Meier survival, principal component, receiver operating characteristic (ROC) curve, and nomogram analyses. In addition, the potential functions of lncRNAs in the novel signature were explored through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses and gene set enrichment analysis (GSEA). Finally, in both risk groups and subtypes classified based on the expression of the risk-related lncRNAs, we analyzed the immune characteristics and drug sensitivity of patients. Results: After rigorous screening processes, we built a model based on 11 m7G-related lncRNAs for predicting patient overall survival (OS). The results suggested that the survival status of patients with high risk scores was lower than that of patients with low risk scores, and a high risk score was related to malignant clinical features. Cox regression analysis showed that the m7G risk score was an independent prognostic parameter. Moreover, immune cell infiltration and immunotherapy sensitivity were different between the two risk groups. Conclusion: The m7G risk model constructed based on 11 m7G-related lncRNAs can effectively assess the OS of HCC patients and may offer support for making individualized treatment and immunotherapy decisions for HCC patients.